Function matters: Coronavirus cross-binding antibodies do not cross-neutralize - Farcet, Maria R.; Schwaiger, Julia; Karbiener, Michael; Kreil, Thomas R. (Frontiers in Medicine, 2022)
Background: During the current pandemic, the Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) neutralization capacity of the immunoglobulin (IG) supply has changed from undetectable for lots manufactured from plasma collected before the pandemic, to now highly potent. Objective: As antibodies induced by exposure to or vaccination against Coronaviruses were shown to be cross-coronavirus reactive, it was of interest to understand whether SARS-CoV-2 neutralizing antibodies would result in increased functional IG potency also against seasonal Coronaviruses. Methods: IG lots from US plasma collected before SARS-CoV-2 emerged and collected during the pandemic were analyzed by live virus neutralization assay for SARS-CoV-2 and seasonal Human coronaviruses (HCoVs) NL63 and OC43 neutralizing antibody content. Results: Pre-pandemic IG showed no SARS-CoV-2 neutralizing antibody titers. However, IG lots produced from plasma of post-coronavirus disease 2019 (COVID-19) individuals exhibited robust anti-SARS-CoV-2 potency (1267 IU/ml) which further increased approximately 4-fold in pandemic IG lots reaching a mean titer of 5122 IU/ml. Nonetheless, neutralizing antibody potencies to the HCoVs NL63 and OC43 remained stable over this period, i.e., have not increased correspondingly. Conclusion: The present results show that cross-Coronavirus-reactive antibodies are not cross-neutralizing, i.e., SARS-CoV-2 antibodies do not neutralize seasonal Coronaviruses NL63 and OC43.